Model Simulasi dalam Mata Kuliah Strategi Pembelajaran Fisika - Satutik Rahayu (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2015)
The simulation model of learning is the application of the principles of cybernetics in education is a human as a control system that is able to generate and control the movement itself through feedback. Learning model simulations applicable in the course of learning strategy with the aim to enable students abilities analogous to the process of cybernetics. The simulation model has four stages: orientation, training for participants, process simulation and stabilization or debriefing. Lecturer in learning tasks with the simulation model is as supportive of observing and helping students deal with problems that arise.